Studi Fenomenologi dalam Kegiatan Shalat Sunnah Malam Jumat di Masjid Tegalsari Jetis Ponorogo - Munsifah (IAIN Madura, 2021)
Tegalsari is the name of a village located in the southeast of the center of Ponorogo City. This area is famous for the religious tourism complex of the Jami 'Tegalsari Mosque and the tomb of a prominent Muslim propagator in Ponorogo named Kiai Ageng Muhammad Besari (Rohmatulloh, 2015). Since the beginning of his move to Tegalsari, many religious and teaching activities have been carried out. Several activities, both daily, weekly, monthly and yearly, are still routinely carried out at the Tegalsari Mosque until now (Pramono, 2020). Among the weekly activities routinely carried out at the Tegalsari Mosque are the Friday night sunnah prayer activities. In the sunnah prayer activity on this Friday night, of course, there are messages of both implied and explicit preaching. This preaching activity at Tegalsari Mosque is a type of preaching bil-hal. With activities like this, it is hoped that the people who carry out the sunnah prayer will not only carry it out ceremonially but also be able to understand, appreciate, and carry out the da'wah messages contained in it so that it can add to the value of faith and devotion to Allah SWT and to increase syiarity. Islam in Tegalsari in particular and other areas as widely as possible. This study uses a qualitative method with a phenomenological approach. The informants in this study were determined using purposive sampling technique with data collection techniques in the form of in-depth interviews and document search activities. The results of this study indicate that the Friday night sunnah prayer activities at the Tegalsari Mosque contain a message that the implementation of worship will be more special and provide peace of mind if the congregation as the performer of worship feels a solid heart when performing it. The background that supports the implementation of the Friday night sunnah prayer activities at Tegalsari Mosque is the location of the mosque which is in the religious tourism area of the Kiai Ageng Muhammad Besari Tomb. Meanwhile, the obstacle is the Covid-19 pandemic, which has limited social activities, including Friday night sunnah prayers at the Tegalsari Mosque. Key words: Phenomenology Studies, Rituals, Meaning, Religious Tourism.